Factors that explain placement decisions for students with multiple disabilities: findings from national data. Issue 2 (28th April 2016) - Banerjee, Rashida; Sundeen, Todd; Hutchinson, Susan R.; Jackson, Lewis
Abstract : The Special Education Elementary Longitudinal Study data set was utilised to examine the potential influences on placement decisions for students with multiple disabilities in the US. The sample consisted of 415 students. Specifically, the study investigated whether factors including students' prior special education experiences, parental involvement, parental expectations and educational risk factors explain the placement of students in classrooms. Results indicate significant relations between the explanatory variables and the hours spent daily in general education classrooms. However, only two variables, parents' education and receipt of early childhood special education services, were significantly associated with the dichotomised outcome of whether or not a child received any academic instruction in a general education classroom. Research limitations and implications for future research, policy and practice in the international context are discussed.